Snake venom meets oncology: unraveling the anticancer potential of crotamine - Jacob, Beatriz; Alberghini-Dos-Santos, João; Ferreira, Isabela; Vieira, Beatriz; Malachias-Pires, Geovanna [UNESP]; Cerni, Felipe; Pucca, Manuela [UNESP]; Arantes, Eliane; Oliveira, Isadora (Elsevier, 2025)
Cancer remains a significant global health challenge, prompting the search for novel therapeutic strategies that minimize the limitations of current treatments. Crotamine, a cationic myotoxin isolated from the venom of Crotalus durissus spp., has emerged as a promising anticancer candidate due to its selective cytotoxicity toward tumor cells and multifaceted biological activities. This review examines the structural and functional characteristics of crotamine, emphasizing its mechanisms of action, such as disruption of ionic homeostasis through calcium influx, inhibition of voltage-gated potassium channels (Kv), and its preferential uptake by proliferating cells as a cell-penetrating peptide (CPP). Moreover, crotamine facilitates the intracellular delivery of bioactive compounds, enhancing drug selectivity and efficacy. Preclinical studies have demonstrated its ability to inhibit tumor growth both in vitro and in vivo, with minimal toxicity to normal tissues and low immunogenicity. These features position crotamine as a strong candidate for anticancer drug development. However, further investigation is essential to fully elucidate its molecular targets and mechanisms and to support its clinical translation.